Linking reduced deforestation and a global carbon market: Impacts on costs, financial flows, and technological innovation - Valentina Bosetti; Ruben Lubowski; Alexander Golub; Anil Markandya (Fondazione Eni Enrico Mattei (FEEM), 2009)
Discussions over tropical deforestation are currently at the forefront of climate change policy negotiations at national, regional, and international levels. This paper analyzes the effects of linking Reduced Emissions from Deforestation and Forest Degradation (REDD) to a global market for greenhouse gas emission reductions. We supplement a global climate-energy-economy model with alternative cost estimates for reducing deforestation emissions in order to examine a global program for stabilizing greenhouse gas concentrations at 550 ppmv of CO2 equivalent. Introducing REDD reduces global forestry emissions through 2050 by 20-22% in the Brazil-only case and by 64-88% in the global REDD scenarios. At the same time, REDD lowers the total costs of the climate policy by an estimated 10-25% depending on which tropical countries participate and whether the banking of excess credits for use in future periods is allowed. As a result, REDD could enable additional reductions of at least 20 ppmv of CO2-equivalent concentrations with no added costs compared to an energy-sector only policy. The cost savings from REDD are magnified if banking is allowed and there is a need to increase the stringency of global climate policy in the future in response, for example, to new scientific information. Results also indicate that REDD decreases carbon prices in 2050 by 8-23% with banking and 11-26% without banking. While developing regions, particularly Latin America, gain the value of REDD opportunities, the decrease in the carbon price keeps the value of international carbon market flows relatively stable despite an increase in volumes transacted. We also estimate that REDD generally reduces the total portfolio of investments and research and development of new energy technologies by 1-10%. However, due to impacts on the relative prices of different fossil fuels, REDD has a slight positive estimated effect on investments in coal-related technologies (IGCC and CCS) as well as, in some cases, non-electric energy R&D. This research confirms that integrating REDD into global carbon markets can provide powerful incentives for the preservation of tropical forests while lowering the costs of global climate change protection and providing valuable policy flexibility.
Keywords: Q23; Q24; Q42; Q52; Q54; Q55; 330; Carbon Market; Climate Change; Innovation; Mitigation; Policy Costs; Offsets; Reduced Emissions from Deforestation and Degradation (REDD); Technological Change; Tropical Deforestation